Performance of rutting, stripping and cracking of warm mix asphalt. (May 2019) - Naqibah, S. N.; Hainin, M. R.; Idham, M. K.; Warid, M. N. M.; Hassan, N. A.; Mohamed, A.; Puan, O. C.; Ismail, C. R.
Abstract: Hot Mix Asphalt (HMA) is a conventional mixtures and widely used in Malaysia. Emissions of Carbon Dioxide (CO2) during production of HMA due to high temperature give bad impact to the environment. During construction, cool weather is one of the factor that will easily influence the HMA mixtures where it will cause the reduction of temperature during compaction. This factor will affect the compaction process for the pavement which the most important part for road construction. It will reduce the density of the pavement and also the strength which cause shorter life span, rutting, cracking and stripping. Therefore, in this study, Warm Mix Asphalt (WMA) is one of the methods to overcome these issues. This study investigated the performance WMA in term of rutting, cracking and stripping incorporating different percentages of additives namely Evotherm (ET) and Evoflex (EF) with 0.3%, 0.4% and 0.5% by weight of bitumen. These additives were used to lower the mixing and compaction temperature of asphalt mixture. Asphalt mixture with nominal maximum aggregate size 14 mm (AC 14) with 5.3% optimum bitumen content were used in this study. The optimum additive content was evaluated based on the Marshall, Modified Lottman, Indirect Tensile Strength (ITS), and Asphalt Pavement Analyser (APA) tests. The results revealed that 0.4 % ET and 0.3 % EF additives were considered as optimum additive content. Both 0.4 % ET and 0.3 % EF gave better performance in stripping and rutting resistance. However, in cracking performance, 0.4 % ET was more susceptible in cracking compared with 0.3 % EF.